2016
DOI: 10.2337/db15-1493
|View full text |Cite
|
Sign up to set email alerts
|

Dual Actions of Apolipoprotein A-I on Glucose-Stimulated Insulin Secretion and Insulin-Independent Peripheral Tissue Glucose Uptake Lead to Increased Heart and Skeletal Muscle Glucose Disposal

Abstract: Apolipoprotein A-I (apoA-I) of HDL is central to the transport of cholesterol in circulation. ApoA-I also provides glucose control with described in vitro effects of apoA-I on β-cell insulin secretion and muscle glucose uptake. In addition, apoA-I injections in insulin-resistant diet-induced obese (DIO) mice lead to increased glucose-stimulated insulin secretion (GSIS) and peripheral tissue glucose uptake. However, the relative contribution of apoA-I as an enhancer of GSIS in vivo and as a direct stimulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…Whether this is also the case for b-DKO mice treated acutely with a single injection of apoA-I remains to be determined. However, because a single 14 mg/kg apoA-I injection has been reported to improve GSIS in normal and high-fat fed C57BL6 mice (16), it seems reasonable to assume that apoA-I may have a similar effect in b-DKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this is also the case for b-DKO mice treated acutely with a single injection of apoA-I remains to be determined. However, because a single 14 mg/kg apoA-I injection has been reported to improve GSIS in normal and high-fat fed C57BL6 mice (16), it seems reasonable to assume that apoA-I may have a similar effect in b-DKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma HDL cholesterol levels are associated with a reduced risk of developing cardiovascular disease (13). We and others have reported that HDLs and apolipoprotein A-I (apoA-I), the main HDL apolipoprotein, also have antidiabetic properties (14)(15)(16). In addition to increasing insulin synthesis and improving insulin secretion in b cells, HDLs and apoA-I alleviate insulin resistance by increasing glucose uptake into skeletal muscle (14,16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both HDLs and apoA-I increase the synthesis and secretion of insulin in pancreatic beta cells (112,113). They also enhance glucose uptake by skeletal muscle (114)(115)(116), and thus improve insulin sensitivity. An increase in either, or both, of these HDL functions in people treated with a CETP inhibitor could explain the improvement in glycemic control and decreased risk of developing diabetes that was observed in these studies.…”
Section: Reveal Trial With Anacetrapibmentioning
confidence: 99%
“…The main differences between ApoA-1 deficiency and MDCO-216 treatment in mice exposed to cigarette smoke were that ApoA-1 deficiency caused a significant loss in both lean and fat mass, while MDCO-216 treatment markedly increased lean mass, leaving fat mass unaffected. ApoA-1 is known to affect numerous metabolic functions, including the stimulation of glucose uptake by skeletal muscle [26,27]. It has also been shown that ApoA-1 can increase mitochondrial biogenesis in vitro in myotubes [28].…”
Section: Discussionmentioning
confidence: 99%